2015
DOI: 10.15287/afr.2015.356
|View full text |Cite
|
Sign up to set email alerts
|

Application of 13C NMR spectroscopy to characterize organic chemical components of decomposing coarse woody debris from different climatic regions

Abstract: . Application of 13 C NMR spectroscopy to characterize organic chemical components of decomposing coarse woody debris from different climatic regions. Ann. For. Res. 58(1): 3-13.Abstract. Solid-state 13 C nuclear magnetic resonance (NMR) spectroscopy was applied to coarse woody debris (CWD) in different stages of decomposition and collected from forest floor of a subtropical, a cool temperate, and a subalpine forest in Japan. The purpose was to test its applicability to characterize organic chemical compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…During decaying processes, soluble C in active organic C of dead wood is consumed for microorganism demand (Anderson & Dousch 1989), while passive C fraction is slowly decomposing because of its accumulation in persistent organic matter of lignin (Bonanomi et al 2013). Similar to finding of Hishinuma et al (2015), increased lignin-C content and decreased polysaccharide-C were found in advanced decay of wood in this study. The abundance of dead wood mass and stocks of lignin, C, and N were dominated by early decayed wood which might reflect a low decay process intensity of the woody debris in our plots.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…During decaying processes, soluble C in active organic C of dead wood is consumed for microorganism demand (Anderson & Dousch 1989), while passive C fraction is slowly decomposing because of its accumulation in persistent organic matter of lignin (Bonanomi et al 2013). Similar to finding of Hishinuma et al (2015), increased lignin-C content and decreased polysaccharide-C were found in advanced decay of wood in this study. The abundance of dead wood mass and stocks of lignin, C, and N were dominated by early decayed wood which might reflect a low decay process intensity of the woody debris in our plots.…”
Section: Discussionsupporting
confidence: 90%
“…2C and 2D). Substrate quality and microbial activity probably enhanced N concentration in advanced decaying dead wood through (1) N translocation from immobilized soil nutrient mediated by microorganisms i.e., fungi (Philpott et al 2014), (2) increased activity of asymbiotic N-fixing bacteria (Brunner & Kimmins 2003) and (3) increased N structural binding with lignin, aromatic and phenolic compounds which were resistant to be degraded (Hishinuma et al 2015). In our study, neither lignin nor C concentrations differed maredly among wood decay stages ( Fig.…”
Section: Discussionmentioning
confidence: 54%
“…The slight increase in carbon concentration at lower wood densities is consistent with the findings for other temperate and boreal conifer species. Preston et al ( 1998Preston et al ( , 2006 and Hishinuma et al (2015) reported increasing carbon concentration with higher decay classes for (Sandstrom et al 2007) and Estonia (Koster et al 2015) showed the same trend. Sakai et al (2012) found that dead wood of Japanese cedar (Cryptomerajaponica) D. Don.…”
Section: Wood Density As a Means To Quantify Carbon Densitymentioning
confidence: 55%
“…From the end of the 19th century (Wollny, 1902) to modern times (e.g. Hishinuma et al, 2015), there has been considerable research aiming to determine the relations between the characteristics of the OM and decomposition processes, nutrient release and soil improvement. Many different approaches have been used, which range from tracer experiments and modelling (Pansu et al, 2014) to laboratory tests and analytical measurements such as biochemical fractionation and spectrometry (Kögel-Knabner, 1997;Pansu & Gautheyrou, 2006).…”
Section: Introductionmentioning
confidence: 99%